Temperature dependent striction effect in a single crystalline Nd2Fe14B revealed using a novel high temperature resistivity measurement technique. (1st May 2022) - Cho, Kyuil; Bud'ko, S L; Canfield, P C
Abstract: We studied the temperature dependence of resistivity in a single crystalline Nd2 Fe14 B using a newly developed high temperature probe. This novel probe employs mechanical pin connectors instead of conducting glue/paste. From warming and cooling curves, the Curie temperature was consistently measured around T c = 580 K. In addition, anomalous discrete jumps were found only in cooling curves between 400 and 500 K, but not shown in warming curves. More interestingly, when the jumps occurred during cooling, the resistivity was increased. This phenomenon could possibly be due to a temperature dependent striction effect induced by the re-orientation of magnetic domains well below the Curie temperature. Further microscopic study is needed to confirm this effect.